Upaya Pengolahan Dan Pemanfaatan Air Limbah Domestik Pada Stasiun Pengisian Bulk Elpiji di PT X - Muhammad Aditya Muzaky; Rizka Novembrianto (Jurnal Universal Technic, 2024)
In the wastewater industry, it is divided into 2, specifically wastewater from home activities and production. Domestic activity wastewater comes from all worker sanitation activities and industrial supporting facilities such as prayer rooms, canteens and toilets. Waste water from these activities must be treated first so that it does not pollute the surrounding environment. PT X is an industry that operates in the field of bulk LPG filling stations which has made efforts to process and also utilize 100% of the waste water from its domestic activities. Sewage Treatment Plants handle the processing (STP) facilities with chemical and biological processes which are able to reduce pollutant parameters such as BOD, COD, TSS, Ammonia and Total Coliform by 90%, 85%, 95%, 90% and 99.9% and have been meet the specified quality standards. Meanwhile, oil & fat parameters are not too focused because they still meet existing quality standards, Therefore, processing aims to lower the relatively high organic characteristics. The results of this processing will be reused to reduce the use of clean water for irrigating green open spaces and roads.